2021
DOI: 10.1017/s2040174420001348
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving adversity during infancy and preschool cognitive function: adaptations to context?

Abstract: From a conditional adaptation vantage point, early life caregiving adversity likely enhances aspects of cognition needed to manage interpersonal threats. Yet, research examining early life care and offspring cognition predominantly relies upon experiments including affectively neutral stimuli, with findings generally interpreted as “early-life caregiving adversity is, de facto, ‘bad’ for cognitive performance.” Here, in a Southeast Asian sample, we examined observed maternal sensitivity in infancy and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 81 publications
3
14
0
Order By: Relevance
“…There were no associations between violence exposures and reasoning performance. Overall, this study suggests that ecologically relevant testing materials may, in some conditions, “level the playing field” for adversity‐exposed youth (Ellis et al, 2020; Frankenhuis, Young, et al, 2020; Rifkin‐Graboi et al, 2021; VanTassel‐Baska, 2018).…”
Section: Unpredictability Violence Poverty 1 2 3 4 5 6 7 8 9 10mentioning
confidence: 82%
“…There were no associations between violence exposures and reasoning performance. Overall, this study suggests that ecologically relevant testing materials may, in some conditions, “level the playing field” for adversity‐exposed youth (Ellis et al, 2020; Frankenhuis, Young, et al, 2020; Rifkin‐Graboi et al, 2021; VanTassel‐Baska, 2018).…”
Section: Unpredictability Violence Poverty 1 2 3 4 5 6 7 8 9 10mentioning
confidence: 82%
“…This point has been repeatedly made in psychology journals (e.g., Keller et al, 2018;Rogoff et al, 2017;Sternberg, 2014), and has been the focus of work by evolutionary developmental psychologists (e.g., Barrett, 2020;Bjorklund & Ellis, 2014;Geary & Berch, 2016;House et al, 2013;Legare, 2019). Reaching out from the other side of the bridge, clinical psychologists have connected their work with that of biological anthropologists and evolutionary psychologists (e.g., Callaghan & Tottenham, 2016;Ganz, 2018;Richardson et al, 2019;Rifkin-Graboi et al, 2021;Tooley et al, 2021). Particularly relevant is a recent paper by Humphreys and Salo (2020), which argues that developmental and clinical psychologists need to empirically update their notions of the expected human childhood in a way that better aligns with the high and variable levels of adversity documented in the historical and cross-cultural record.…”
Section: Child-centeredness Across Societiesmentioning
confidence: 92%
“…This finding is consistent with the observation that not all aspects of cognitive flexibility are negatively impacted by exposure to ELA. Some researchers have suggested that experiencing ELA may provide individuals with some cognitive benefits [ 68 , 71 ], including improved detection of dangers. Considering the limited amount of research on this topic, future research should consider examining associations between ACEs and cognitive benefits.…”
Section: Discussionmentioning
confidence: 99%